Socio-environmental perceptions and practices in the communities surrounding the Organic Corridor Montes del Aguacate (Research, Society and Development, 2021)
The Biological Corridor Montes del Aguacate in Costa Rica is a connectivity zone where a close relationship between human populations and the environment is generated, which directly impacts natural ecosystems. The socio-environmental study is built from the viewpoint of its inhabitants so a perception survey is applied with open and closed questions to 128 people in 30 districts where the biological corridor is located. The categories of analysis deal with: 1) land use and sustainable productive activities; 2) local organization and training in environmental issues; and 3) practices aimed at environmental protection. Two relevant productive activities are identified in the biological corridor: coffee cultivation and cattle raising, which mobilize the local economy, but at the same time, generate significant tree felling and some polluting actions. There is a general lack of knowledge among the participating population about the coexistence with the biological corridor. The discourse of caring for the natural environment prevails, but is not accompanied by concrete actions. The development of the area is strongly linked to rural tourism, where the scenic beauty and natural biodiversity are taken advantage of. Community recognition of the water management authorities, the awareness of some inhabitants with actions for a sustainable environment and the power that some communities have rediscovered as a collective in the protection of the natural environment are rescued.